High-strength degradable composite material with concentric wood-like annual ring structure and preparation method and application thereof
Patent Information
- Application Number
- CN202311725102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-15
AI Technical Summary
同时可吸收材料进行实际使用或测试的时候,往往在强度方面存在较大的缺陷,导致螺钉由于应力失效而发生断裂
[0035](1)本发明的螺钉同时以甲基丙烯酰化海藻酸钠、光引发剂、磷酸三钙(TCP)、羟基磷灰石(HA)、氧化石墨烯(GO)、生物活性玻璃(BAG)等人造骨原料作为原料,同时结合原位浇铸、三重固化、旋转干燥、螺纹加工等组合工艺制得,通过利用不同直径的圆柱体互相套嵌以可控构建同心仿木年轮结构来实现材料力学性能的增强,同时通过添加具有成骨功能的人工骨材料来增强植入材料的生物相容性和成骨性能。
Smart Images

Figure CN117958939B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical device technology, specifically to a high-strength biodegradable composite material with a concentric wood-ring-like structure, its preparation method, and its application. Background Technology
[0002] Internal fixation of broken bones in humans or animals can be achieved using internal fixation devices. Screw fixation has been used to treat fractures for over a century, and its techniques have evolved to include a wide variety of screws, from ordinary screws to screws with different pitches and lengths, to cannulated screws, hip screws, expansion screws, double-ended threaded screws, locking screws, micro-moving screws, and even screws designed for specific locations (such as pedicle screws) or made of special materials (such as absorbable screws). It can be used alone or as an essential component in conjunction with various other fixation systems (such as plate-and-screw systems or intramedullary nail systems).
[0003] With the advancement of fracture trauma diagnosis and treatment concepts and technologies, the requirements for the manufacturing and processing of internal fixation devices are constantly being updated. The morphology and function of screws have also undergone significant changes. Existing metal screw materials essentially only serve a fixation function, with virtually no osteogenic effect. Furthermore, metal screw materials are non-degradable, requiring secondary surgery, which imposes a significant physiological, psychological, and economic burden on patients. Therefore, a major current development direction is to research and develop a screw material that is biodegradable in vivo and possesses osteogenic activity, reducing patient suffering. Currently, most technologies involve blending osteogenic substances such as tricalcium phosphate and bioactive glass with polymers such as polylactic acid and PLGA to prepare absorbable materials with osteogenic functions. However, during actual use or testing, absorbable materials often exhibit significant strength deficiencies, leading to screw breakage due to stress failure.
[0004] Therefore, providing a high-strength, osteogenic, and biodegradable composite material and its preparation method is a problem that needs to be solved by those skilled in the art. Summary of the Invention
[0005] The purpose of this invention is to propose a high-strength biodegradable composite screw with a concentric wood-ring structure and its preparation method. This invention utilizes the interlocking of cylinders of different diameters to controllably construct a concentric wood-ring structure to enhance the mechanical properties of the material. At the same time, it enhances the biocompatibility and osteogenic properties of the implant material by adding artificial bone material with osteogenic function.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A high-strength biodegradable composite material with a concentric wood-ring-like structure includes an inner core and several layers of wood-ring-like layers covering the inner core.
[0008] Preferably, the inner core is porous hydroxyapatite.
[0009] Preferably, the porous hydroxyapatite has a pore size of 300-600 μm, and the presence of the pore size helps the absorbable material suspension to penetrate into the porous hydroxyapatite core.
[0010] Preferably, the raw materials for the wood-ring-like layer include inorganic materials, sodium methacrylamide, and a photoinitiator;
[0011] The mass ratio of the inorganic material, the sodium methacryloylated alginate, and the photoinitiator is 2-10:4-15:0.05-0.07.
[0012] Alginate methacryloyl (AlgMA) hydrogels possess a three-dimensional structure suitable for cell growth and differentiation, and both -OH and -COOH in the structural units can serve as chemically active sites. In addition, AlgMA hydrogels exhibit good mechanical properties, and the 3D microscaffolds constructed from them possess tunable mechanical and chemical properties.
[0013] Preferably, the inorganic material is at least one of tricalcium phosphate, hydroxyapatite, graphene oxide, and bioactive glass;
[0014] The grafting degree of the methacryloylated sodium alginate is 25-90%;
[0015] The photoinitiator is at least one of LAP, photoinitiator 1173, Irgacure-2959, and VA086.
[0016] Preferably, the tricalcium phosphate and hydroxyapatite have a particle size of 200-500 nm, the graphene oxide has a diameter of 5-10 μm, and the bioactive glass has a diameter of 50-150 nm.
[0017] The preparation method of a high-strength biodegradable composite material with a concentric wood-ring structure described above includes the following specific steps: with the inner core as the center, at least two partitions are placed sequentially on the outer periphery; a suspension of the wood-ring layer raw material is sequentially cast into the gaps between the inner core and the partitions, and between the partitions, to obtain a colloidal mold; then, after ultrasonic treatment, triple curing, deionized water dialysis, and drying, a high-strength biodegradable composite material with a concentric wood-ring structure is obtained.
[0018] The mechanical performance principle of the concentric wood-like annual ring structure of the biodegradable composite material of this invention is as follows: The polymethacrylamide sodium alginate and hydroxyapatite (HA) core grow interlaced, forming a good mechanical bond. Simultaneously, the triple curing method further promotes the cross-linking reaction of the polymethacrylamide sodium alginate, increasing the bonding strength between the polymer and the artificial bone material. Furthermore, the chelation effect of carboxyl groups and calcium ions further enhances the bending performance of the composite material. In addition, the tubular structure of the annual rings provides greater stability under bending forces. The interaction of reducing self-weight and enhancing internal shear effect results in stronger bending resistance. The multi-layered annual ring structure further enhances the bending resistance of the composite material. Moreover, the tubular structure of the annual rings also helps to change the direction of crack propagation during failure, thereby absorbing some energy and improving mechanical properties. The comprehensive performance of all these aspects results in the strong mechanical properties of this composite material.
[0019] Preferably, the suspension is prepared by mixing sodium methacrylamide and a photoinitiator evenly under light-protected conditions, then adding inorganic materials to the above solution, shaking for 5-15 minutes, sonicating for 5-10 minutes at an ultrasonic power of 60-100W, mixing evenly, and then centrifuging at a low speed of 2000-3000 rpm to remove bubbles, thereby obtaining the suspension.
[0020] Preferably, the specific steps of the triple curing process are as follows:
[0021] (1) First curing: After irradiating the colloidal mold with ultraviolet light for 3-10 seconds, remove all of the glass cylindrical spacers except the outermost layer and let stand for 5-10 minutes;
[0022] (2) Secondary curing: After the first curing, the colloidal mold is irradiated with ultraviolet light for 5-15 minutes to fully cure;
[0023] (3) Triple curing: Remove the outermost glass cylindrical partition layer of the colloidal mold after double curing, and then crosslink it with calcium ion solution.
[0024] Preferably, the inner core is cylindrical with a diameter of 1-2 mm.
[0025] Preferably, the thickness of the partition is 50-100 μm.
[0026] Preferably, the ultraviolet light is a cylindrical ultraviolet light device with an ultraviolet light power of 100W;
[0027] The concentration of the calcium ion solution is 5-15 wt%, and the calcium ion solution is at least one of calcium chloride, calcium nitrate, and calcium dihydrogen phosphate.
[0028] The cross-linking time is 4-6 hours.
[0029] Preferably, the concentration of sodium methacrylamide in the suspension is 4-15 wt%, the concentration of photoinitiator is 0.05-0.07 wt%, and the amount of inorganic material added is 2-10 wt%.
[0030] Preferably, the ultrasonic parameters are: ultrasonication in a 60°C water bath for 3-5 minutes, ultrasonic power of 30-60W, in order to make the material more uniform and remove air bubbles generated by oscillation.
[0031] The drying process is a rotary drying method, with a rotation speed of 20-40 revolutions per minute, a temperature controlled at 50-60℃, and a time of 24-72 hours.
[0032] The deionized water dialysis time is 12-24 hours to remove free calcium ions and unreacted photoinitiators.
[0033] Applications of high-strength biodegradable composite materials with concentric wood-ring structures as described above, or high-strength biodegradable composite materials with concentric wood-ring structures prepared by the methods described above, in the field of orthopedic nails.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The screw of the present invention uses artificial bone materials such as sodium methacrylamide, photoinitiator, tricalcium phosphate (TCP), hydroxyapatite (HA), graphene oxide (GO), and bioactive glass (BAG) as raw materials. It is made by combining in-situ casting, triple curing, rotary drying, and thread processing. The mechanical properties of the material are enhanced by using cylinders of different diameters to interlock with each other to controllably construct a concentric wood-like annual ring structure. At the same time, the biocompatibility and osteogenic properties of the implanted material are enhanced by adding artificial bone materials with osteogenic function.
[0036] (2) The concentric wood-ring structure composite screw of the present invention has high strength and is biodegradable. It also has the advantages of high bending strength, promoting bone function, biosafety and biodegradability in vivo, which meet the needs of orthopedic implant fixation.
[0037] (3) The use of the glass cylindrical partition and the triple curing process of the present invention are mutually dependent and synergistic: the glass cylindrical partition mold first provides a central fixing point for the inner core, and then provides space between the partitions for in-situ casting of the solution. The first light curing can partially solidify the sodium alginate solution, and at the same time provide the possibility for filling the interlayer space and mutual penetration between the interlayer solutions after demolding; the second light curing can completely solidify the absorbable material suspension; the third curing uses calcium ions to form an "egg-box" structure with the carboxyl groups on the sodium alginate molecular chain to consolidate the crosslinking density and improve the bending strength of the material; the design of the above mold structure and the design of the triple curing process are all customized for the preparation scheme of the high-strength biodegradable composite screw with concentric wood ring structure in the present invention, and have obvious originality.
[0038] (4) The present invention uses a porous hydroxyapatite core and a rotary drying process to help shape the screw and prevent bending during the drying process. The core plays a guiding and shaping role, and the rotary drying process allows the screw surface to be heated sequentially and dehydrated evenly, ultimately resulting in a straight screw.
[0039] (5) The high-strength biodegradable composite screw with concentric wood-ring structure in this invention is enhanced from four levels to meet the strength requirements of orthopedic internal fixation: 1) At the molecular level, the cross-linking between double bonds and the ion chelation of carboxyl groups and calcium ions form an "egg-box" structure; 2) The nanomaterials such as tricalcium phosphate (TCP), hydroxyapatite (HA), graphene oxide (GO), and bioactive glass (BAG) added to the solution promote bone formation and enhance the screw matrix through nanocomposite reinforcement; 3) The use of glass cylindrical spacers and multiple curing processes enables the construction of a concentric wood-ring structure; 4) The inner core of the middle screw provides central support for the entire screw.
[0040] (6) The tricalcium phosphate, bioactive glass and hydroxyapatite used in this invention are all bioactive materials with excellent osteoconductivity and osteoinductive properties, which promote bone tissue growth and repair; sodium methacrylamide is a biocompatible and biodegradable material with little tissue irritation. As the body gradually absorbs the absorbable material, no secondary surgery is required, which reduces the patient's pain. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings in this description are merely embodiments of the present invention.
[0042] Figure 1 This is a structural diagram of the colloid mold of Embodiment 1 of the present invention;
[0043] Figure 2 This is a structural diagram of the cylindrical ultraviolet light device according to Embodiment 1 of the present invention;
[0044] Figure 3 These are structural diagrams of the screws used in the embodiments and comparative examples of the present invention;
[0045] Figure 4 The images show the osteogenic differentiation results of the embodiments and control examples of the present invention. Detailed Implementation
[0046] Embodiments of the present invention are described below, examples of which are shown in the accompanying drawings. The embodiments described with reference to the drawings are exemplary and intended to explain the present invention, but are not to be construed as limiting the present invention.
[0047] Example 1
[0048] This invention provides a method for preparing a high-strength biodegradable composite screw with a concentric wood-ring-like structure, comprising the following specific steps:
[0049] (1) Under light-protected conditions, the mixed solution of sodium methacrylamide (10wt%) and Irgacure-2959 photoinitiator (0.06wt%) was completely dissolved in a water bath at 60℃. Then, bioactive glass (6wt%) was added to the above solution. The above composite suspension was shaken with Vortex for 10min, and then sonicated for 8min with an ultrasonic power of 80W. After mixing evenly, the mixture was centrifuged at 2500 rpm for 5min to remove bubbles, and a suspension of wood ring layer raw material was obtained.
[0050] (2) A cylindrical porous hydroxyapatite core with a pore size of 300 μm, a length of 10 cm, and a diameter of 2 mm was 3D printed. Three transparent glass cylindrical partitions (50 μm thick) with different diameters were evenly placed around the porous hydroxyapatite core. The diameters were 10.0 mm, 15 mm, and 20.0 mm, respectively. The prepared absorbable material suspension was poured between the glass partitions (the surfaces in contact with the absorbable material suspension were uniformly coated with glycerol in advance to facilitate the removal of the concentric mold later) and the hydroxyapatite core. Then, the mixture was poured outwards into the gaps between the glass partitions to obtain a colloidal mold. The structure is as follows: Figure 1 Then the entire mold was placed in an ultrasonic 60℃ water bath and ultrasonicated for 4 minutes with an ultrasonic power of 50W.
[0051] (3) Triple curing: First curing, using a cylindrical 100W ultraviolet light device (structure as shown in the figure) Figure 2Irradiate the colloidal mold prepared in step (2) for 7s to partially solidify the sodium alginate solution. Then slowly pull the concentric mold upwards, leaving only the outermost glass film to maintain the cylindrical shape, and obtain a colloidal mold with a multi-layered concentric cylindrical structure. Let it stand for 8min to allow the incompletely solidified absorbable material suspension between the concentric cylindrical colloids to fuse with each other and fill the space between the concentric cylindrical colloids.
[0052] Double curing, then continue to irradiate for 10 minutes using a cylindrical 100W ultraviolet light device to completely cure the absorbable material suspension;
[0053] Triple curing involves removing the outermost glass cylindrical partition from the double-cured colloidal mold, immersing the resulting cylinder in a 10wt% calcium chloride solution, and performing calcium ion crosslinking for 5 hours.
[0054] The cylinder was then removed and dialyzed in deionized water for 18 hours (with the solution changed every 3 hours). The resulting multilayer concentric cylindrical gel material was then rotary dried at 55°C and 30 rpm for 48 hours to obtain the final multilayer concentric cylindrical rod. The rod was then shaped and fabricated into implantable medical devices such as screws. Specific design details are provided in [link to design details]. Figure 3 This results in a high-strength biodegradable composite screw with a concentric wood-ring-like structure.
[0055] Example 2
[0056] This invention provides a method for preparing a high-strength biodegradable composite screw with a concentric wood-ring-like structure, comprising the following specific steps:
[0057] (1) Under light-protected conditions, the mixed solution of sodium methacrylamide (4wt%) and LAP photoinitiator (0.05wt%) was completely dissolved in a water bath at 60℃. Then, tricalcium phosphate (2wt%) was added to the above solution. The above composite suspension was shaken with Vortex for 5min, and then sonicated for 5min with an ultrasonic power of 80W. After mixing evenly, the mixture was centrifuged at 2500 rpm for 5min to remove bubbles, and a suspension of wood ring layer raw material was obtained.
[0058] (2) A cylindrical porous hydroxyapatite core with a pore size of 600 μm, a length of 10 cm and a diameter of 1 mm was 3D printed. Four transparent glass cylindrical partitions with different diameters (thickness of 50 μm) were evenly placed around the porous hydroxyapatite core. The diameters were 10 mm, 15 mm, 20 mm and 25 mm respectively. The prepared suspension was poured between the glass partitions (the surface in contact with the suspension was uniformly coated with glycerol in advance to facilitate the removal of the concentric mold later) and the hydroxyapatite core. Then, the suspension was poured outward in the gaps between the glass partitions to obtain a colloidal mold. The entire mold was then placed in an ultrasonic 60℃ water bath for 3 min and the ultrasonic power was 30 W.
[0059] (3) Triple curing: First curing, using a cylindrical 100W ultraviolet light device (structure as shown in the figure) Figure 2 Irradiate the colloidal mold prepared in step (2) for 10 seconds to partially solidify the sodium alginate solution. Then slowly pull the concentric mold upwards, leaving only the outermost glass film to maintain the cylindrical shape, and obtain a colloidal mold with a multi-layered concentric cylindrical structure. Let it stand for 5 minutes to allow the incompletely solidified absorbable material suspension between the concentric cylindrical colloids to fuse with each other and fill the space between the concentric cylindrical colloids.
[0060] Double curing, then continue to irradiate for 5 minutes using a cylindrical 100W ultraviolet light device to completely cure the absorbable material suspension;
[0061] Triple curing involves removing the outermost glass cylindrical partition from the double-cured colloidal mold, immersing the resulting cylinder in a 5wt% calcium chloride solution, and performing calcium ion crosslinking for 4 hours.
[0062] The cylinder was then removed and dialyzed in deionized water for 18 hours (with the solution changed every 3 hours). The resulting multilayer concentric cylindrical gel material was then rotary dried at 50°C and 20 rpm for 48 hours to obtain the final multilayer concentric cylindrical rod. The rod was then shaped and fabricated into implantable medical devices such as screws. Specific design details are provided in [link to design details]. Figure 3 This results in a high-strength biodegradable composite screw with a concentric wood-ring-like structure.
[0063] Example 3
[0064] This invention provides a method for preparing a high-strength biodegradable composite screw with a concentric wood-ring-like structure, comprising the following specific steps:
[0065] (1) Under light-protected conditions, the mixed solution of sodium methacrylamide (15wt%) and photoinitiator 1173 (0.07wt%) was completely dissolved in a water bath at 60℃. Then, hydroxyapatite (10wt%) was added to the above solution. The above composite suspension was shaken with Vortex for 15min, and then sonicated for 10min with an ultrasonic power of 80W. After mixing evenly, the mixture was centrifuged at 2500 rpm for 5min to remove bubbles, and a suspension of wood ring layer raw material was obtained.
[0066] (2) A cylindrical porous hydroxyapatite core with a pore size of 400 μm, a length of 10 cm, and a diameter of 1 mm was 3D printed. Five transparent glass cylindrical partitions with different diameters (thickness of 50 μm) were evenly placed around the porous hydroxyapatite core. The diameters were 10 mm, 15 mm, 20 mm, 25 mm, and 30 mm, respectively. The prepared suspension was poured between the glass partitions (the surface in contact with the suspension was uniformly coated with glycerol in advance to facilitate the removal of the concentric mold later) and the hydroxyapatite core. Then, the suspension was poured outward in the gaps between the glass partitions to obtain a colloidal mold. The entire mold was then placed in an ultrasonic 60°C water bath for 5 min with an ultrasonic power of 60 W.
[0067] (3) Triple curing: First curing, using a cylindrical 100W ultraviolet light device (structure as shown in the figure) Figure 2 Irradiate the colloidal mold prepared in step (2) for 10 seconds to partially solidify the sodium alginate solution. Then slowly pull the concentric mold upwards, leaving only the outermost glass film to maintain the cylindrical shape, and obtain a colloidal mold with a multi-layered concentric cylindrical structure. Let it stand for 10 minutes to allow the incompletely solidified absorbable material suspension between the concentric cylindrical colloids to fuse with each other and fill the space between the concentric cylindrical colloids.
[0068] Double curing, then continue to irradiate for 15 minutes using a cylindrical 100W ultraviolet light device to completely cure the absorbable material suspension;
[0069] Triple curing involves removing the outermost glass cylindrical partition from the double-cured colloidal mold, immersing the resulting cylinder in a 5wt% calcium chloride solution, and performing calcium ion crosslinking for 6 hours.
[0070] The cylinder was then removed and dialyzed in deionized water for 18 hours (with the solution changed every 3 hours). The resulting multilayer concentric cylindrical gel material was then rotary dried at 60°C and 40 rpm for 48 hours to obtain the final multilayer concentric cylindrical rod. The rod was then shaped and fabricated into implantable medical devices such as screws. Specific design details are provided in [reference needed]. Figure 3 This results in a high-strength biodegradable composite screw with a concentric wood-ring-like structure.
[0071] Compare with Example 1
[0072] A method for manufacturing a screw includes the following specific steps:
[0073] (1) Prepare 50 mL of a mixed solution of sodium methacrylamide (10 wt%) and photoinitiator Irgacure-2959 (0.06 wt%) in a 60 °C water bath under light-protected conditions. Shake the above composite suspension with Vortex for 10 min, then sonicate for 8 min with an ultrasonic power of 80 W. After mixing evenly, centrifuge at 2500 rpm for 5 min to remove bubbles and obtain a suspension.
[0074] Steps (2) and (3) are the same as in Example 1, resulting in a screw;
[0075] Compare with Example 2
[0076] A method for manufacturing a screw includes the following specific steps:
[0077] (1) Under light-protected conditions, the mixed solution of sodium methacrylamide (10wt%) and Irgacure-2959 photoinitiator (0.06wt%) was completely dissolved in a water bath at 60℃. Then, bioactive glass (6wt%) was added to the above solution. The above composite suspension was shaken with Vortex for 10min, and then sonicated for 8min with an ultrasonic power of 80W. After mixing evenly, the mixture was centrifuged at 2500 rpm for 5min to remove bubbles, and a suspension of wood ring layer raw material was obtained.
[0078] (2) The prepared suspension was poured into a transparent glass cylindrical container with a height of 10cm and a diameter of 2cm. The mold filled with the sodium methacrylamide alginate composite suspension was irradiated with a cylindrical 100W ultraviolet light device for 10 minutes to completely solidify the sodium methacrylamide alginate composite suspension. The transparent cylindrical glass mold was removed, and the resulting cylindrical gel material was rotary dried at 55℃ at a rotation speed of 30 rpm for 48 hours to obtain the final cylindrical rod. The obtained rod was then shaped and prepared into implantable medical devices such as screws. For specific design, see [link to design details]. Figure 3 This results in a type of screw;
[0079] The relevant performance tests were performed on the screws of Example 1 and the screws of Control Examples 1-2, and the results are as follows:
[0080] Bending strength: The bending strength of the composite screw in Example 1 was 407.8 MPa, while the bending strength of the control screw in Example 2 was 215.1 MPa;
[0081] Example 1 407.8 Example 2 512.4 Example 3 628.1 Compare with Example 1 427.6 Compare with Example 2 215.1
[0082] Biocompatibility: The CCK-8 results of the composite screw and bone mesenchymal stem cells co-cultured for 7 days in Example 1 showed that the biocompatibility was 89.3% compared to the blank control (well plate), demonstrating that the material has good biocompatibility.
[0083] Degradation performance: After 28 days of in vitro degradation experiment, the composite screw in Example 1 had a remaining mass of 43.6%, which proves that the material has excellent degradation performance;
[0084] Osteogenic Properties: After 14 days of osteogenic induction differentiation experiments (materials were placed in the upper layer of a Transwell chamber, BMSCs were placed in the lower layer of the chamber, and cultured in osteogenic differentiation medium for 14 days), ALP and ARS staining results showed that, compared with Control 1, the bone mesenchymal stem cells of the Example 1 composite screw exhibited a higher osteogenic differentiation tendency. Specific results are shown below. Figure 4 .
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength biodegradable composite material with a concentric wood-ring-like structure, characterized in that, It includes an inner core and several layers of wood-like annual rings covering the inner core; The inner core is porous hydroxyapatite; the pore size of the porous hydroxyapatite is 300-600 μm; The raw materials for the wood-ring-like layer include inorganic materials, sodium methacrylamide alginate, and photoinitiator. The mass ratio of the inorganic material, the sodium methacryloylated alginate, and the photoinitiator is 2-10:4-15:0.05-0.
07. The inorganic material is at least one of tricalcium phosphate, hydroxyapatite, graphene oxide, and bioactive glass. The grafting degree of the methacryloylated sodium alginate is 25-90%; The photoinitiator is at least one of LAP, photoinitiator 1173, Irgacure-2959 and VA086; The preparation method of the high-strength biodegradable composite material with concentric wood ring structure includes the following specific steps: with the inner core as the center, at least two partitions are placed sequentially on the outer periphery; a suspension of the wood ring layer raw material is sequentially cast into the gaps between the inner core and the partitions and between the partitions to obtain a colloidal mold; then, after ultrasonic treatment, triple curing, deionized water dialysis, and drying, a high-strength biodegradable composite material with concentric wood ring structure is obtained. The specific steps of the triple curing process are as follows: (1) First curing: After irradiating the colloidal mold with ultraviolet light for 3-10 seconds, remove all the glass cylindrical partitions except the outermost layer and let it stand for 5-10 minutes; (2) Secondary curing: After the first curing, the colloidal mold is irradiated with ultraviolet light for 5-15 minutes to fully cure; (3) Triple curing: Remove the outermost glass cylindrical partition layer of the colloidal mold after double curing, and then crosslink it with calcium ion solution.
2. The high-strength biodegradable composite material with a concentric wood-ring-like structure according to claim 1, characterized in that, The ultraviolet light is emitted using a cylindrical ultraviolet light device with an ultraviolet light power of 100W; The concentration of the calcium ion solution is 5-15 wt%, and the calcium ion solution is at least one of calcium chloride, calcium nitrate, and calcium dihydrogen phosphate. The cross-linking time is 4-6 hours.
3. The high-strength biodegradable composite material with a concentric wood-ring-like structure according to claim 1, characterized in that, The concentration of sodium methacryloyl alginate in the suspension is 4-15 wt%, the concentration of photoinitiator is 0.05-0.07 wt%, and the amount of inorganic material added is 2-10 wt%.
4. The high-strength biodegradable composite material with a concentric wood-ring-like structure according to claim 1, characterized in that, The ultrasonic parameters are: ultrasonication in a 60℃ water bath for 3-5 minutes, ultrasonic power of 30-60W; The drying process is a rotary drying process, with a rotation speed of 20-40 revolutions per minute, a temperature controlled at 50-60℃, and a time of 24-72 hours. The deionized water dialysis time is 12-24 hours.
5. The application of the high-strength biodegradable composite material with concentric wood-ring-like structure as described in any one of claims 1-4 in the field of orthopedic nails.
Citation Information
Patent Citations
Assembled root-type dental implant with osteogenesis promoting and anti-inflammatory effects, and manufacturing method of assembled root-type dental implant
CN111671533A
Polycaprolactone / sodium alginate composite material as well as preparation method and application thereof
CN112239567A
All-natural polysaccharide-based degradable composite bone nail material with oriented-concentric circle structure and preparation method of all-natural polysaccharide-based degradable composite bone nail material
CN114870099A
Concentric, functionally gradient material for living body
JP2008307071A